Perancangan Character Merchandising Creative IP VICOLIO dengan Motif Batik Nusantara - Shienny Megawati Sutanto (Universitas Multimedia Nusantara, 2022)
Batik is one of the Indonesian cultures recognized by UNESCO as a Humanitarian Heritage for Oral and Intangible Culture. With the recognition of batik by UNESCO, the image of batik is elevated both domestically and internationally. This opens up opportunities for batik craftsmen in Indonesia to make batik creations, not just as traditional formal clothes. The government through KEMENPAREKRAF continues to make efforts to develop a creative economy based on intellectual property works or creative IP. As a concrete manifestation to support the government's efforts as well as the learning process based on real cases, students majoring in Visual Communication Design at Ciputra University (VCD-UC) researched and developed assets from VCD-UC's creative IP, VICOLIO into character merchandising with batik pattern. The method used in this research is design thinking which includes observation, ideation, design, and prototyping. The results of this research are four VICOLIO character patterns that are applied into a tote bag design. Each character is adapted into Indonesian batik patterns from various islands in Indonesia. Strix Jalowy is inspired by the island of Java, Alces Gumantar is inspired by the island of Papua, Castor Arjana is inspired by the island of Java, and Canis Trunyan is inspired by the island of Bali. To increase the value of VICOLIO batik pattern, an Augmented Reality application is added so users can interact virtually with the product. The Augmented Reality application is also used to inform the user about the origin and inspiration for each character's batik patterns. Keywords: motif; batik; creative IP; vicolio